Human Capital Development in Ghana - Tanaka, Tomomi (World Bank, Washington, DC, 2020)
To achieve inclusive economic growth, Ghana must continue to build its human capital and ensure children are healthy, developmentally on track, and acquiring skills to thrive in a fast-changing world. This report identifies critical challenges Ghana faces in pursuing further human capital development and inclusive growth: Ghana’s progress against child stunting (low height for age) has been significant, however, disparities across regions and between children in rich and poor households are substantial; cognitive development among Ghanaian children under 5 compares favorably to its peers. However, there exist large disparities across regions and income groups; even though Ghana’s enrollment rates at primary and junior secondary school are relatively high compared with its peers, Ghanaian children’s test scores are extremely low compared with not only other Lower-Middle Income Countries, but also other Sub-Saharan African countries; and Ghana’s enrollment rates at senior secondary school and higher education remain low compared with peer countries of similar income levels.